Flow Around A Thin Profile With A Two-Phase Medium With Solid Particles (Journal of Pharmaceutical Negative Results, 2023)
This article examines the problem of the effect of particles on a wedge. The structure of shock waves of a two-Phase Current is studied and the trajectory of particles is determined after the impact.A flow model around a thin profile is proposed by a two-phase medium, taking into account the effect of reflecting particles from a solid surface. The problem is solved in a linear formula under different assumptions. Calculations are made for the initial parameters, and the results are presented graphically.